Efficacy and liver function preservation with donafenib combined with transarterial chemoembolization in unresectable hepatocellular carcinoma: An ALBI grade analysis - Li, Jinpeng; Li, Yan; Li, Yuanming; Du, Jiasheng; Zhao, Lujun; Zhong, Jingtao (Frontiers in Oncology, 2025)
PurposeThis study evaluated the hepatoprotective effects and safety profile of donafenib combined with transarterial chemoembolization (TACE) in unresectable hepatocellular carcinoma (HCC) through analysis of albumin-bilirubin (ALBI) score modifications.Patients and methodsWe enrolled 36 patients with unresectable HCC receiving donafenib+TACE, with or without immune checkpoint inhibitors. ALBI grades were assessed at baseline and throughout treatment, with statistical analyses examining associations between ALBI grade changes, tumor response, and survival outcomes.ResultsOur prospective analysis demonstrated significant antitumor efficacy with favorable hepatic safety. The regimen achieved objective response and disease control rates of 69.4% and 91.7%, respectively, with median progression-free survival of 10.7 months and median time to response of 1.4 months, indicating rapid therapeutic onset. Hepatic function remained stable throughout treatment, with consistent ALBI grades from baseline to progression/final follow-up (−2.41 ± 0.41 vs. −2.45 ± 0.52, P=0.67). Among patients, 58.3% maintained stable hepatic function, while 25.0% improved from ALBI grade 2 to 1. Hepatic function deterioration occurred less frequently in responders than nonresponders (12.0% vs. 27.3%). ALBI grade modification emerged as a potential predictive biomarker (AUC=0.665). Patients with ALBI grade below the −0.18 threshold achieved superior clinical outcomes, including higher response rates (84.6% vs. 56.5%) and longer progression-free survival (not reached vs. 5.63 months, P=0.017). These findings establish hepatic function preservation as both a safety indicator and efficacy predictor for donafenib+TACE therapy.ConclusionThe combination of donafenib and TACE demonstrates favorable hepatic function preservation while maintaining therapeutic efficacy. ALBI grade improvement is correlated with enhanced treatment response and survival outcomes, indicating potential synergistic benefits for tumor control and hepatic function preservation.